Mastering Machine Learning for Penetration Testing: Develop an Extensive Skill Set to Break Self-Learning Systems Using Python - Chebbi, Chiheb (Packt Publishing, Limited, 2018)
We live in an era where cyber security plays an important role. As systems are getting smarter, we now see machine learning interrupting computer security. With the adoption of machine learning in upcoming security products, it's important for pentesters and security researchers to understand how these systems work, and to breach them for.